Prenatal Differential Diagnosis and Prospective Management of Hydranencephaly: Diagnosis Diferensial Prenatal dan Manajemen Prospektif dari Hidranensefali - Hermawan, Gezta N.; I. Nym. Gde. D. Mahardhika; Jennie D. Sutantio; Dyana S. Velies (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objective: To report a rare case of hydranencephaly that was diagnosed during prenatal period. We also provided further review of differential diagnosis and management performed in Ende District General Hospital, based on appropriate literatures and guidelines available. Methods: Case Report Case: A 27-year old primigravida women was diagnosed with term pregnancy (37 weeks of gestation) and intra-uterine singleton live fetus with hydranencephaly via ultrasonography. In this patient, emergency caesarean section (CS) was performed to prevent complication of cephalo-pelvic disproportion (CPD), involving teamwork between obstetrics and perinatology. A male neonate was born weighing 3000 grams, head circumference of 32 cm, and APGAR score of 2/4/7/8 suggestive of asphyxia and respiratory distress. The newborn was immediately transferred to Neonatal Intensive Care Unit (NICU) for further resuscitative management and observation. The newborn remains in stable condition after resuscitative management was given. Post-natal transcranial sonography (TCS) of the newborn was performed by a pediatrician, and the diagnosis of hydranencephaly was confirmed. The newborn was later referred to facilities with neurosurgery department for further evaluation and intervention. Conclusion: Early prenatal recognition of hydranencephaly and exclusion of similar differential diagnosis, which includes: hydrocephalus, holoproscencephaly, porencephaly and schizencephaly, are fundamental in formulating proper multidisciplinary management with pediatric and neurosurgery department, which may consequently improve the newborn’s life expectancy. Keywords: Hydranencephaly, Differential Diagnosis, Management. Abstrak Tujuan: Melaporkan suatu kasus langka hidranensefali yang kami diagnosa dalam periode prenatal; dan memberikan ulasan lanjut mengenai diagnosis diferensial dan manajemen yang kami kerjakan di Rumah Sakit Umum Ende, berdasarkan literatur dan pedoman ilmiah yang tersedia. Methode: Laporan Kasus Kasus: Seorang perempuan primigravida berusia 27 tahun di diagnosa dengan kehamilan aterm (37 minggu gestasi), janin tunggal hidup intrauterin dengan hidranensefali via ultrasonografi. Pada pasien ini dilakukan Sectio Caesarea (SC) cito untuk mencegah komplikasi dari disproporsi kepala-panggul dengan kerjasama tim kebidanan dan perinatologi. Lahir bayi laki-laki dengan berat badan 3000 gram, lingkar kepala 32 cm, dan skor APGAR 2/4/7/8 dengan kesan asfiksia dan distres pernapasan. Bayi segera dipindahkan ke Neonatal Intensive Care Unit (NICU) untuk penanganan resusitatif lanjut dan observasi. Bayi tetap bertahan dalam kondisi stabil setelah diberikan manajemen resusitatif. Pemeriksaan sonografi transkranial paska natal dilakukan oleh dokter anak, dan diagnosis hidranensefali terkonfirmasi. Bayi kemudian di rujuk ke fasilitas dengan ketersediaan departemen bedah saraf untuk evaluasi dan intervensi lanjut. Kesimpulan: Deteksi dini prenatal hidranensefali dan eksklusi diagnosis diferensial serupa, yang mencakup: hidrosefalus, holoprosensefali, porensefali, dan skizensefali, adalah dasar dari formulasi manajemen multidisiplin yang baik antara departemen pediatrik maupun bedah saraf, sehingga dapat meningkatkan kualitas dan ekspektasi hidup bayi baru lahir. Kata Kunci: Hidranensefali, Diagnosis Diferensial, Manajemen